2012
DOI: 10.1590/s1806-83242012000600012
|View full text |Cite
|
Sign up to set email alerts
|

Association between parental guilt and oral health problems in preschool children

Abstract: Parents may feel guilty about their children's oral problems, which can affect their quality of life. The aim of this study was to assess the presence of parental guilt and its association with early childhood caries (ECC), traumatic dental injuries (TDI) and malocclusion (AMT) in preschool children. All 2 to 5 year-old children (N = 305), and their parents, seeking dental care at the University of São Paulo Dental School one-week Screening Programme, were asked to participate in the study, and 260 agreed. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
34
3
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 24 publications
10
34
3
5
Order By: Relevance
“…The incidence of early childhood caries has decreased in recent years; however, the condition is still frequently diagnosed in preschool children [12]. Although some authors have found higher frequency of early childhood caries in boys [13] and others in girls [2], this study showed no predilection for gender, corroborating a previous study [14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidence of early childhood caries has decreased in recent years; however, the condition is still frequently diagnosed in preschool children [12]. Although some authors have found higher frequency of early childhood caries in boys [13] and others in girls [2], this study showed no predilection for gender, corroborating a previous study [14].…”
Section: Discussionsupporting
confidence: 90%
“…The feeling of guilt of caregivers in relation to the oral health condition of their children has been previously related to the severity of lesions [12]. In this study, neither dental caries severity (lesion in enamel or enamel and dentin with or without pulp involvement), nor location (anterior or posterior tooth), were related to the feeling of guilt of caregivers.…”
Section: Discussioncontrasting
confidence: 60%
“…This result may show that the damage caused by nonnutritive sucking habits can be corrected spontaneously after cessation of these habits. 25 The present investigation evaluated the impact of different types of malocclusion on quality of life among preschool children, in contrast to many studies 3,5,13 that confirm this relationship based solely on the presence/absence of this oral disorder. Parents of children with anterior open bite reported negative impacts on most of the ECOHIS domains, with the exception of "symptoms."…”
Section: Discussionmentioning
confidence: 89%
“…12 The majority of studies employing the ECOHIS have not found a significant association between malocclusion and impact on quality of life among preschool children. 2,3,5,13,14,15 However, many studies have considered only the presence/absence of malocclusion in the analysis. Thus, the aim of the present study was to evaluate associations between different types of malocclusion and the impact on the quality of life of preschool children and their families.…”
Section: Introductionmentioning
confidence: 99%
“…While some investigations have found that household income 13 and a mother's education level 7,14,15 exert an influence on the occurrence of TDI in preschoolers, others have not found such associations (Table 1). 1,5,6,11,12,13,14,15,16,17,18,19,20 declaration of interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%